1998
DOI: 10.1247/csf.23.265
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin b2 Induces Differentiation without Growth Inhibition in Cultured B16 Melanoma Cells.

Abstract: ABSTRACT.Treatment with 5 pM of saikosaponin (SS) b2 for 30 days was found to induce differentiation of B16 melanomacells, with potentiation of expressions of melanogenesis and tyrosinase. To explore the mechanism of this effect, we observed the cell growth, cell cycle and morphology, and found that SSb2 did not affect any of these parameters. That is, SSb2 induced the differentiation of B16 melanoma cells without growth inhibition or cytotoxicity under conditions of low dose and long-term treatment. Phorbol e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Sc: saikosaponin C. **P b 0.01, *P b 0.05 vs. control by t-test, n = 3 per group. Chou et al, 2003;Okita et al, 1993;Wu and Hsu, 2001;Wu, 2003;Tsai et al, 2002;Zong et al, 1998;Zong et al, 1996), but saikosaponin C had no relation with cancer cells growth inhibition (Okita et al, 1993). In our study, we found that saikosaponin C induced endothelial cells growth, migration and capillary tube formation, the opposite effect for cancer prevention.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Sc: saikosaponin C. **P b 0.01, *P b 0.05 vs. control by t-test, n = 3 per group. Chou et al, 2003;Okita et al, 1993;Wu and Hsu, 2001;Wu, 2003;Tsai et al, 2002;Zong et al, 1998;Zong et al, 1996), but saikosaponin C had no relation with cancer cells growth inhibition (Okita et al, 1993). In our study, we found that saikosaponin C induced endothelial cells growth, migration and capillary tube formation, the opposite effect for cancer prevention.…”
Section: Discussionmentioning
confidence: 52%
“…However, saikosaponin C contains a trisaccharide of glucose-glucose-rhamnose. Recently, saikosaponins, including saikosaponin A, B2 and D, were reported to have properties of cell growth inhibition, inducing cancer cells differentiation and apoptosis (Hsu et al, 2004;Chen et al, 2003;Chou et al, 2003;Okita et al, 1993;Wu and Hsu, 2001;Wu, 2003;Tsai et al, 2002;Zong et al, 1998;Zong et al, 1996). However, saikosaponin C had no correlation with cell growth inhibition (Okita et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory properties of saikosaponins have been revealed by their inhibition of mouse ear and paw edema induced by phorbol 12-myristate 13-acetate (PMA) in vivo, reduction of cyclooxygenase (COX) and lipoxygenase (LOX) production in vitro [8,9].The immunoregulatory functions of saikosaponins also include the elevation of plasma adrenocorticotropin (ACTH) and corticosterone levels in vivo [10], enhancement of antibacterial plaque-forming cell responses [11], activation of phagocytosis of macrophages [12,13], and inhibition of platelet activation and endothelial cell injury [14]. In fact, apart from the immunoregulatory functions of Saikosaponins, the cytotoxic potential of saikosaponins is also reported in the literature and hence they have been investigated as potential anti-cancer agents [15][16][17][18].…”
Section: Saikosaponins and Their Immunoregulatory Functionsmentioning
confidence: 99%
“…Many studies have reported the presence of various bioactive components in its roots, such as triterpenoid glycosides (saikosaponins), polysaccharides, flavonoid glycosides, phenethyl alcohol glycosides, and isopentenol glycosides . Many phytochemical studies have demonstrated that triterpenoid glycosides (saikosaponins) are a major component of the roots of B. falcatum , which possess various pharmacological activities, including anti‐inflammatory, antihepatitis, and anti‐cancer properties . Thus far, the detection of 20 saponins from the roots of B. falcatum has been reported.…”
Section: Introductionmentioning
confidence: 99%